Cutaneous lesions and finger clubbing uncovering hypocomplementemic urticarial vasculitis and hepatitis C with mixed cryoglobulinemia - Teresa Pinto-Almeida; Mónica Caetano; Rosário Alves; Manuela Selores (Sociedade Brasileira de Dermatologia, 2013)
Urticarial vasculitis is a rare clinicopathologic entity characterized by urticarial lesions that persist for more than 24 hours and histologic features of leukocytoclastic vasculitis. Patients can be divided into normocomplementemic or hypocomplementemic. The authors report the case of a healthy 49-year-old woman with a 1-year history of highly pruritic generalized cutaneous lesions and finger clubbing. Laboratory tests together with histopathologic examination allowed the diagnosis of hypocomplementemic urticarial vasculitis, chronic hepatitis C and type II mixed cryoglobulinemia. The patient started symptomatic treatment and was referred to a gastroenterologist for management of the hepatitis C, with progressive improvement of the skin condition. The development of hypocomplementemic urticarial vasculitis in the context of chronic hepatitis C is exceedingly rare and possible pathogenic mechanisms are discussed.